RESEARCH ANALYZES CRM IN PIZZA HUT MALANG - Nico Arviana; Prima Khrisna (Journal of International Conference Proceedings (JICP), 2018)
This research is conducted on determining the key elements which play their role towards the success of Pizza Hut customer relationship management strategy. The strategy used by the researcher is case study where as the researcher used deductive approach to conduct this research. In addition to this, the research used qualitative data analysis technique to conduct the analysis of the data. The researcher used non probability sampling technique where judgment sampling has been used by the researcher in order to collect the data. The researcher used interview questions where semi structured interviews have been to collect the research data. All the factors which support the CRM philosophy in Pizza Hut Malang have been collected and recommendations have been given on those elements which are not so supportive. Key word : Customer relationship management, Pizza Hut Malang.